Analysis of Islamic Law on The Haijuran Traditions of The Padang Bolak Community in North Padang Lawas Regency - Siregar, Ilham Ramadan; Idris, Idris; Amiruddin, Amiruddin; Akhyar, Akhyar (Program Studi Hukum Keluarga Islam, 2024)
The tradition of haijuran is a traditional practice and customary sanction applied when someone intends to undergo a divorce within the Padang Bolak community, particularly in North Padang Lawas Regency. This tradition has evolved into local wisdom aimed at minimizing divorce cases within the Padang Bolak community and continues to persist to this day. The research is conducted to understand the significance and role of the haijuran tradition, as well as analyzing the Islamic legal aspects related to this tradition. The research method used is field research with a qualitative phenomenological approach. The research findings indicate that the haijuran tradition still exists in the community, despite alternative approaches to handling divorce cases through religious courts. This can be attributed to the strong adherence to traditional values by the Padang Bolak community in the North Padang Lawas regency. The role of the haijuran tradition has proven to be quite effective in minimizing divorce rates in the community. Other contributing factors to this reduction in divorces include high family concerns, adherence to customary rules, intermarriage within the same ethnic and regional groups, and the imposition of haijuran fines. The Islamic legal analysis of the haijuran tradition can be divided into two aspects. Firstly, the designation of haijuran to husbands is categorized as a matter of muamalah (interpersonal), with its legal basis drawn from urf (custom), and its implementation considered mubah (permissible). The method employed in this analysis is istishlah (fiqh discussion) or maslahah mursalah (decision), with the rationale of expected benefits, such as minimizing unilateral divorces and providing compensation to divorced women. On the other hand, the designation of haijuran to women seeking divorce from their husbands has a different legal status, in accordance with Islamic law, known as khulu’ (divorce).